O a(u)tor e suas "interversões" em Retrato desnatural, de Evando Nascimento - Fabíola Padilha (Estudos de Literatura Brasileira Contemporânea)
This paper aims at proposing a reading of the supposedly fictional book Retrato desnatural (diários - 2004 a 2007), by Evando Nascimento, published in 2008, by observing the way through which the author, in consonance with the notion of “writable text” by Roland Barthes, entertains a dialogue with diverse artistic lan- guages (plastic arts, music, theater, cinema, literature) as well as with the western philosophy. It will also be verified that this dialogue, on its turn, flows into the idea of expropriation of the subject, since the author recognizes, under the sign of the "self", the innumerable traces of the others in his writing. The copious "mes" that integrate the manufacturing of the self-portrait, vestiges left by the other in the self, compose an exact image of his innate movability - pantomimes of the author/actor exhibiting multiple interversions, redefining the task of self-reengen- dering through writing, by postulating that "everything then are daily fictions, that is, infictions, slips, rollings of an I and its others. Until when." (Nascimento, 2008, p. 160). Singular snapshots showing us, readers/spectators, their only pos- sible face: an unnatural portrait.